Origins of the Photocurrent Multiplication Effect in the Polythiophene‐Based Photodetectors. Issue 1 (23rd February 2022) - Cao, Yu; Xu, Xinjian; Shen, Lening; Zhang, Dong; Zheng, Jie; Gong, Xiong
Abstract: The photocurrent multiplication (PM) effect has been used to boost the device performance of polymer‐based photodetectors (PDs), but its origin is rarely addressed. In this study, the origins of the PM effect in polymer PDs based on the P3HT:PC71 BM bulk heterojunction (BHJ) composite thin film, where P3HT is poly(3‐hexylthiophene), and PC71 BM is [6, 6]phenyl‐C71 ‐butyric acid methyl ester, through both computational simulation and experimental investigation are reported. Systematic studies indicate that two key factors play an important role in the realization of the PM effect in polymer PDs. One factor is the work function of the metal electrode, and the other is the PC71 BM aggregations at the interface between the P3HT:PC71 BM BHJ composite thin film and the metal electrode. Moreover, the results from both experimental and computational simulation indicate that the values of the current density under light illumination minus the current density in the dark of polymer PDs are increased simultaneously along with the reduction of the thickness of the P3HT:PC71 BM BHJ composite thin film. The results provide an understanding of the PM effect in polymer PDs and guidance for the development of high‐performance polymer PDs based on BHJ composite thin film. Abstract : Through computational simulation and experimental investigation, it is realized that both the work function of the metal electrode and the aggregations of the electron acceptors at the interface between the bulk heterojunction composite thin film and the metal electrode play an important role in the photocurrent multiplication effect that occurs in polymer‐based photodetectors.